Preclinical Testing of a Novel, Additive-Manufactured, Three-Dimensional Porous Titanium Structure - Woodard, Erik; Post, Zach; Morrison, Mark (Structural Integrity of Additive Manufactured Materials and Parts, 2020)
When considering orthopedic implants for bone growth, several factors such as porosity, pore size, stiffness, friction, and strength can affect bone growth and contribute to the long-term success of the implant. Additive manufacturing is one tool to help achieve the ideal factors for implant structures and materials. Smith+Nephew has developed an additive manufactured (AM), Ti-6Al-4V advanced porous structure designed to be similar to cancellous bone with up to 80% porosity. This structure is currently used as part of both acetabular shells and augments. This paper describes the preclinical testing of this advanced porous structure that comprised coupon-level and device-level testing. The critical parameters that can influence bone ingrowth, such as pore size (mean void intercept length, or MVIL) and porosity, were measured. The ability of the three-dimensional porous structure to withstand compressive, tensile, and shear forces was evaluated in static (monotonic) testing. Finally, bone ingrowth was assessed in a load-bearing ovine model. Clinically relevant device-level fatigue testing was conducted in foam blocks with a cavity and adjacent rim defect to simulate the acetabulum. The strength of the locking screw hole features was assessed using static and fatigue cantilever bending and pull-through strength. Acetabular constructs were also fatigue tested in an unsupported model with an adjacent augment and corresponding defect. Constructs completed all clinically relevant fatigue testing with no fractures.